2018
DOI: 10.3390/coatings8090307
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Cavitation Erosion Resistance of HVOF Deposited WC-Co Coatings with Different Sized WC

Abstract: Conventional, multimodal and nanostructured WC-12Co coatings with different WC sizes and distributions were prepared by high velocity oxy-fuel spray (HVOF). The micrographs and structures of the coatings were analyzed by scanning electron microscope (SEM), X-ray diffractometer (XRD) et al. The porosity, microhardness and fracture toughness of the WC-Co coatings were measured. The coating resistance to cavitation erosion (CE) was investigated by ultrasonic vibration cavitation equipment and the cavitation mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…On the other hand, the size of the WC particles in the WC-17Co coating was uniform and smaller than the WC-12Co coating. Some studies [11,18] have indicated that a smaller WC particle size is desirable in decreasing porosity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the size of the WC particles in the WC-17Co coating was uniform and smaller than the WC-12Co coating. Some studies [11,18] have indicated that a smaller WC particle size is desirable in decreasing porosity.…”
Section: Discussionmentioning
confidence: 99%
“…To improve the CE resistance of material, high-velocity air fuel [7], high-velocity oxygen fuel (HVOF) [8], arc spraying [9], atmospheric plasma spraying [10], and other surface modification technologies had been developed. Due to the optimal combination of mechanical strength (hardness and fracture toughness), HVOF-sprayed WC-Co-based ceramic-metal (cermet) composites coatings can improve CE resistance [11,12]. Lamana et al [13] demonstrated that an increase in Co content could lead to an increase in the fracture toughness and CE resistance of WC-Co coatings, which also resulted from the increase in compressive residual stress.…”
Section: Introductionmentioning
confidence: 99%
“…Cobalt based materials are among the most cavitation erosion-resistant materials commercially available and chemical composition of Stellite 6 alloy exhibits excellent cavitation erosion (CE) resistance. Therefore, Stellite 6 superior CE behaviour is documented by many scientific papers, for the stellites produced as alloy weld overlays [17], plasma transferred arc (PTA) overlay welding [18], laser cladding [11], shielded metal arc welding (SMAW) [19] and also HVOF deposited Stellite 6 coatings [20] and cobalt-based WC-Co cermet's deposits [21][22][23]. Unfortunately, as far as the authors' knowledge no paper describes cavitation properties of the powder metallurgy satellites and analysis its cavitation wear behaviour of HIPed Stellite 6.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with atmospheric plasma spraying, the molten powder particles in HVOF are faster, have higher momentum and lower temperature, and do not evaporate when they hit the substrate, so the HVOF spraying process is suitable for achieving superhard alloy coatings. (8)(9)(10)(11)(12) This deposition process has little environmental impact and is regarded as the most promising substitute for hard chrome plating; indeed, the US Federal Aviation Administration has approved this process for spraying many parts of aircraft engines. (13) The temperature generated by HVOF spraying can reach 2000-3000 ℃.…”
Section: Introductionmentioning
confidence: 99%